Endoscopic Endonasal Approach for Resection of Suprasellar Hemangioblastoma: Selective Pituitary Sacrifice and Use of Indocyanine Dye: 2-Dimensional Operative Video. Issue 1 (19th August 2020) - Abhinav, Kumar; Gimenez, Patricio; Tyler, Matthew; Patel, Zara M; Fernandez-Miranda, Juan C
Abstract: Suprasellar hemangioblastomas are rare lesions occurring sporadically or more commonly with von Hippel Lindau disease (VHLD). 1, 2 A 27-yr-old female presented with amenorrhea, mildly raised prolactin levels and otherwise normal pituitary function, homonymous hemianopia, and mild cognitive decline. Imaging revealed a large suprasellar lesion arising from the infundibulum, causing compression of optic chiasm with edema in the visual pathways. Lesion appeared hypervascular with prominent feeding vessels from the internal carotid arteries bilaterally. To access these vessels derived from the superior hypophyseal arteries and allow early devascularization, endoscopic endonasal approach was performed. 3 Stalk preservation was deemed unlikely. After opening of the suprasellar dura, indocyanine dye allowed early identification of the feeding vessels. They were sequentially sacrificed, allowing early devascularization while preserving the normal blood supply to the optic chiasm from the superior hypophyseal arteries. Pituitary gland and stalk were removed with the latter being completely involved by tumor to provide access to the retroclival region and posterior circulation. After opening of the dura underlying the dorsum sella, inferior pole of the tumor was exposed with blood supply identified from the posterior communicating arteries but not the basilar or posterior cerebral arteries. Devascularized lesion was safely removed from the optic apparatus, hypothalamus, and the third ventricle. Histology was consistent with hemangoblastoma (VHLD negative). Patient's cognitive and visual function normalized with a postoperative magnetic resonance imagingdemonstrating complete resection, no ischemic events on diffusion-weighted imaging, and resolution of the edema in the hypothalamus and visual pathways. 1 She was started on desmopressin and replacement therapy for pituitary function. The patient consented to the procedure.  Patient provided consent for publication.